Evaluation methods of mineral oil biological pollution - Бойченко, С.В.; Кучма, Н.М. (Proceedings of National Aviation University (archive), 2004)
The review of the literature has shown, that all mineral oil evaluation methods can be classified on two groups: long-term and express-method. the research of existing mineral oil biological pollution has permitted to formulate a conclusion that by dominant methods is long-term, which basic lacks are their large complexity and labouriousness. important there is express-evaluation of aviation fuel biological pollution. аdvisable there is elaboration of an operative effective procedure of aviation fuel biological test. with the purpose of practical realization of the developed technique necessary there is an introduction of quality coefficient «presence microflora» to the list of parameters, that characterize quality aviation fuel.